Predicting Factors of Breast Cancer Prevention Behavior among Muslim Women - Srichoompu , Pimvipa; Kongvattananoa, Puangpaka; Kummabutr, Jeeraporn (Journal of The Royal Thai Army Nurses, 2025)
This study aims to describe the breast cancer prevention behavior and to examine factors predicting the breast cancer prevention behavior among Muslin women. The factors were perceived susceptibility, perceived seriousness, perceived benefits, perceived self-ability, and social support. The samples, randomized by cluster sampling and simple random sampling, were 105. The statistic was descriptive, Chi square and Multiple Linear Regression Analysis. The results showed that the average score for the breast cancer prevention behavior Muslim women was the moderate level (3.40, SD=1.11). Factors that significantly predicted the breast cancer prevention behavior among Muslin women were perceived susceptibility of breast cancer (β = .298, p < .05) and social support (β= .452, p < .05). The total variance explained by these factors among the sample was 43.8 percent (R2 = .438, F(2,104) = 39.687, p < .05) The conclusion of study showed the two significant factors effect to the breast cancer prevention behavior among Muslin women. So, effectiveness of health promotion should concern two factors.